NCS-1 associates with adenosine A2A receptors and modulates receptor function - Navarro, Gemma; Hradsky, Johannes; Lluis, Carmen; Casado, Vicent; McCormick, Peter J.; Kreutz, Michael R.; Mikhaylova, Marina (Frontiers in Molecular Neuroscience, 2012)
Modulation of G protein-coupled receptor (GPCR) signalling by local changes in intracellular calcium concentration is an established function of Calmodulin which is known to interact with many GPCRs. Less is known about the functional role of the closely related neuronal EF-hand Ca2+-sensor proteins that frequently associate with calmodulin targets with different functional outcome. In the present study we aimed to investigate if a target of calmodulin – the A2A adenosine receptor, is able to associate with two other neuronal calcium binding proteins, namely NCS-1 and caldendrin. Using bioluminescence resonance energy transfer and co-immunoprecipitation experiments we show the existence of A2A - NCS-1 complexes in living cells whereas caldendrin did not associate with A2A receptors under the conditions tested. Interestingly, NCS-1 binding modulated downstream A2A receptor intracellular signalling in a Ca2+-dependent manner. Taken together this study provides further evidence that neuronal Ca2+-sensor proteins play an important role in modulation of GPCR signalling.